Reinvestigation of environmental Kuznets curve with ecological footprints: Empirical analysis of economic growth and population density. Issue 1 (3rd September 2020) - Hussain, Muzzammil; Usman, Muhammad; Khan, Jawad Ahmad; Tarar, Zahid Hassan; Sarwar, Muhammad Arslan
Abstract : A large population is not only the burden to a country's economy but can be a threat to the environment. However, the role of the population density in the quality of the environment is silent in the literature. On this note, the current study focuses on the effect of population density on ecological footprints in Pakistan for the period from 1981 to 2016 in the framework of EKC theory. The result from the autoregressive distributive lag model summarized that the effect of population density on ecological footprint is negative and statistically significant, implying that population density does not contribute to environmental degradation. No causality is evident in economic development and ecological footprint. Unlike others, the findings of this study suggest that if the population is suitably spread, it can help to reduce environmental degradation. Moreover, policymakers need to reconsider the density of the population to avoid an ecological deficit.